Levels, Source Apportionment and Health Risk Assessment of Polycyclic Aromatic Hydrocarbons in Soils Around Selected Petrol Filling Stations in Kogi State, Nigeria - Julius Attah Kadili; Godwin John; Ishaq Shaibu Eneji; Adams Udoji Itodo; Rufus Sha'Ato (FUDMA Journal of Sciences, 2026)
Soils around petrol filling stations are exposed to polycyclic aromatic hydrocarbons (PAHs) from fuel spillage, storage tank leakage, and incomplete combustion of petroleum products. This study assessed the levels, distribution, sources and health risk of the 16 USEPA priority PAHs in soils around petrol filling stations in Kogi Central (Zone 1: Ajaokuta, Okene) and Kogi West (Zone 2: Obajana, Lokoja), Kogi State, Nigeria. Twelve soil samples from filling stations and four controls were analyzed using Gas Chromatography-Mass Spectrometry (GC-MS). Surrogate (o-terphenyl) recoveries ranged from 94.0 to 101.6%. Total PAH (Σ16PAHs) concentrations ranged from 0.540 to 5.90 µg/kg, with mean values of 2.55 µg/kg in Zone 1 and 3.45 µg/kg in Zone 2 (combined mean 3.00 µg/kg). A two-sample t-test showed significantly higher PAH concentrations at filling stations than controls (t = -2.30, p = 0.038), with no significant difference among the four towns (p = 0.094). Low molecular weight (2-3 ring) PAHs dominated the distribution (65.7%), followed by 4-ring (30.2%) and 5-6 ring PAHs (4.12%). All individual and total PAH concentrations were below the Dutch maximum permissible concentrations, indicating unpolluted soils. Diagnostic ratios (LMW/HMW = 1.91; Ant/(Ant+Phe) = 0.77; Flt/(Flt+Pyr) = 0.90; BaA/(BaA+Chr) = 0.68) revealed a predominantly pyrolytic origin for the PAHs, with a minor petrogenic contribution. The mean benzo[a]pyrene equivalent concentration (BaPeq) was 0.0595 µg/kg, far below the 600 µg/kg Canadian soil quality guideline, denoting low carcinogenic potential. The results supply baseline data for PAH monitoring in the study area and complement previously published data for Kogi East.